TEACHER’S POLITENESS STRATEGY IN EFL CLASSROOM AND THE EFFECTS ON THE LEARNING PROCESS (A Case Study at SMA Mardhatillah NW Penakak in the School Year 2014/2015) - ZAENUL FIKRI (LPPM Universitas Gunung Rinjani, 2020)
This study was intended to describe politeness strategies in teacher and students interactionin EFL classroom and the effects on the learning process. The researcher chooses to getdata from the eleventh grades of SMA Mardhatillah NW Penakak in the School Year2014/2015. The subjects were the entire participant in EFL classroom (teacher and students)with number of participants were 28 participants. The data of this study was naturalisticsetting; it means that the researcher took the data without manipulating the teaching andlearning process. The data analyzed following Miles & Huberman (1994) an interactivecyclical model of qualitative data analysis was done with three concurrent flows activity,namely data reduction, data display and conclusion drawing/verification. The researcher hadfound four politeness strategies; bald on record, positive politeness, negative politeness andoff record. Based on the result of the finding, the researcher was concluding that the teacherhad positive politeness in teaching learning process. The teacher also used polite utterancesand the teacher character was care, fun and friendly. Most of students in the class hadpositive politeness; they respected their teacher during the teaching and learning process.Key Words: Politeness Strategies , EFL ClassroomPenelitian ini dimaksudkan untuk menggambarkan strategi kesantunan dalam interaksi gurudan siswa di EFL kelas dan efek pada proses pembelajaran. Peneliti memilih untukmendapatkan data dari nilai kesebelas SMA Mardhatillah NW Penakak di Tahun Sekolah2014/2015. Subyek penelitian seluruh peserta dalam EFL kelas (guru dan siswa) denganjumlah peserta 28 peserta. Data dari penelitian ini adalah naturalistik pengaturan; itu berartibahwa peneliti mengambil data tanpa memanipulasi proses pengajaran dan pembelajaran.Data dianalisis berikut Miles & Huberman (1994) model siklus interaktif analisis datakualitatif dilakukan dengan aktivitas tiga arus bersamaan, yaitu reduksi data, display datadan penarikan kesimpulan / verifikasi. Peneliti telah menemukan empat strategi kesantunan;botak pada catatan, kesopanan positif, kesantunan negatif dan off the record. Berdasarkanhasil temuan, peneliti itu menyimpulkan bahwa guru memiliki kesantunan positif dalamproses belajar mengajar. Guru juga digunakan ucapan sopan dan karakter guru ituperawatan, menyenangkan dan ramah. Sebagian besar siswa di kelas memiliki kesantunanpositif; mereka dihormati guru mereka selama proses belajar mengajar.Keywords : Strategi Kesantunan, Kelas EFL